2015
DOI: 10.1186/s13613-015-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of presepsin for the diagnosis of sepsis from SIRS: a systematic review and meta-analysis

Abstract: BackgroundSepsis is a common condition that has a high mortality and morbidity that need prompt diagnosis and treatment. Biomarkers like Soluble CD14 subtype (sCD14-ST, presepsin) may be useful in identifying patients with sepsis and its diagnostic superiority has been confirmed by several preliminary studies. The aim of this study was systematically and quantitatively to evaluate the value of presepsin for the diagnosis of sepsis through the method of meta-analysis.MethodsFour major databases, including MEDLI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 53 publications
2
34
0
3
Order By: Relevance
“…Performance of presepsin corresponds to those reported in non-cirrhotic septic patient populations. In a recent meta-analysis of Zheng et al[41], comprising a total of 8 studies and 1757 patients, the AUC of the summary ROC (SROC) was 0.82. In contrast, weak predictive power of CRP with an AUC-ROC of 0.64 was reported for the infections in critically ill patients with cirrhosis in intensive care unit (ICU)[22], which is also in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Performance of presepsin corresponds to those reported in non-cirrhotic septic patient populations. In a recent meta-analysis of Zheng et al[41], comprising a total of 8 studies and 1757 patients, the AUC of the summary ROC (SROC) was 0.82. In contrast, weak predictive power of CRP with an AUC-ROC of 0.64 was reported for the infections in critically ill patients with cirrhosis in intensive care unit (ICU)[22], which is also in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…(14,15) The wide range of PSP levels among studies may be due to the selection bias of the subjects or the method of PSP measurement. (2,16) We measured PSP with chemiluminescent enzyme immunoassay method which is the most used method in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In ICU patients, presepsin demonstrated diagnostic capacity in differentiating sepsis severity and prognostic value in mortality [156], while Masson et al [157] found that presepsin measured on the first day in ICU in patients with severe sepsis or septic shock was higher in nonsurvivors compared to survivors, thus exhibiting useful prognostic importance. In 2015, three large meta-analyses concluded that presepsin has moderate diagnostic capacity for the detection of sepsis and it is an effective adjunct biomarker, but is insufficient to detect or rule out sepsis when used alone [158][159][160].…”
Section: Presepsinmentioning
confidence: 99%